2005
DOI: 10.1111/j.1740-8261.2005.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Total Anomalous Pulmonary Venous Connection in a Foal

Abstract: An 8-day-old Arabian-Morgan cross colt underwent cardiac evaluation. The foal was tachycardic, tachypneic, exercise intolerant and had a loud right-sided heart murmur and cyanotic mucous membranes. Total anomalous pulmonary venous connection was diagnosed with echocardiography and confirmed at postmortem examination. Total anomalous pulmonary venous connection is a very rare congenital cardiac abnormality that has not been reported before in the horse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Standard transthoracic 2D, M-mode and Doppler techniques were adapted from the mature horse and measurements first reported for Thoroughbred and pony foals in 1984 (Lombard et al 1984;Stewart et al 1984). Since that time, published reports involving the echocardiographic evaluation of the foal have primarily focused on cases of congenital cardiac defects (Pipers et al 1985;Reef et al 1987;Sojka 1987;Wilson and Haffner 1987;Ecke et al 1991;Hinchcliff and Adams 1991;Chaffin et al 1992;Schober et al 2000;Seco Diaz et al 2005;Sleeper and Palmer 2005;Schmitz et al 2008) with occasional case descriptions of acquired cardiac disease (Reef 1987;Collatos et al 1990). However, the utility of echocardiography is not restricted to the diagnosis of anatomical abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Standard transthoracic 2D, M-mode and Doppler techniques were adapted from the mature horse and measurements first reported for Thoroughbred and pony foals in 1984 (Lombard et al 1984;Stewart et al 1984). Since that time, published reports involving the echocardiographic evaluation of the foal have primarily focused on cases of congenital cardiac defects (Pipers et al 1985;Reef et al 1987;Sojka 1987;Wilson and Haffner 1987;Ecke et al 1991;Hinchcliff and Adams 1991;Chaffin et al 1992;Schober et al 2000;Seco Diaz et al 2005;Sleeper and Palmer 2005;Schmitz et al 2008) with occasional case descriptions of acquired cardiac disease (Reef 1987;Collatos et al 1990). However, the utility of echocardiography is not restricted to the diagnosis of anatomical abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study that reviewed 290 dogs with cardiovascular malformations from 1953 to 1965 revealed that only 1 case was diagnosed PAPVC with secundum atrial septal defect [40]. For the published case reports, there are only 3 dogs [41][42][43] and each 1 of chicken [44] and foal [45] that are diagnosed as TAPVC; only 4 dogs [46][47][48] and 2 cats [49,50] are PAPVC. One canine case reported in 1975 did not describe its detail (TAPVC or PAPVC) [51].…”
Section: Anomalous Pulmonary Venous Connectionmentioning
confidence: 99%
“…Signs of dyspnea with exertion, cyanosis and exercise intolerance could be observed, and the patient is at risk of developing to pulmonary hypertension and congestive heart failure. Three veterinary cases were found to have concurrent ASD (secundum type in 1 dog [41] and 1 chicken [44]; sinus venous type in another dog [42]) and the case of foal [45] had concurrent PFO. A special child case had been recognized recently that all of his pulmonary veins were anatomically connected to the left atrium but the blood inside actually was drained into superior vena cava via an innominate vein, therefore corresponded to the definition of supra-cardiac type of anomaly [35].…”
Section: Anomalous Pulmonary Venous Connectionmentioning
confidence: 99%
“…Partial anomalous pulmonary venous connection (PAPVC) is a rare congenital cardiovascular abnormality. In veterinary literature, anomalous pulmonary venous connection (APVC) or drainage has been reported in dogs, [1][2][3][4][5][6][7] cats, 8 a foal, 9 and chickens. 10 In fetal life, the primitive pulmonary veins from the lung buds develop from the splanchnic plexus, which communicates with the systemic venous system, and connects to the left atrium.…”
Section: Introductionmentioning
confidence: 99%